2021
DOI: 10.11114/ijsss.v9i3.5199
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Capital in Educational Context: Lifelong Learning and Beyond Hope

Abstract: The world of work is constantly changing whereby innovation and challenges requires oneself to be competitive. Although, human capital and social capital are vital to the success, psychological capital (PsyCap) has been proposed as a new complementary concept that remains in success. Research proves that hope is a good predictor of subjective well-being. Promoting academic PsyCap helps achieve academic success. The author attempts to draw parallels to consider the construct of PsyCap that can predict education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…PsyCap, as a cognitive-motivational variable, has been linked with several positive outcomes and plays a key role in the relationships between the various school-related factors ( Luthans et al, 2007a ; Siu et al, 2014 ; Kim and Shin, 2021 ; Lin, 2021 ). Similar research has found that positive study-related emotions could enhance students’ learning engagement, academic performance, and achievement ( Villavicencio and Bernardo, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…PsyCap, as a cognitive-motivational variable, has been linked with several positive outcomes and plays a key role in the relationships between the various school-related factors ( Luthans et al, 2007a ; Siu et al, 2014 ; Kim and Shin, 2021 ; Lin, 2021 ). Similar research has found that positive study-related emotions could enhance students’ learning engagement, academic performance, and achievement ( Villavicencio and Bernardo, 2013 ).…”
Section: Introductionmentioning
confidence: 99%